The power of sejarah Indonesia - Joko Darmawan, 1956-; Chaerudin, 1961- (Jakarta : Indonesia Book Project : Distributor tunggal, Buku Kita, 2011)
History of Indonesia.
'Historis book'--V. 1, cover.
Includes bibliographical references (v. 1, p. 219-222).
In Indonesian.
Keywords: Indonesia -- History